2016
DOI: 10.5937/comman11-9514
|View full text |Cite
|
Sign up to set email alerts
|

50 years of Galtung and Ruge: Reflections on their model of news values and its relevance for the study of journalism and communication today

Abstract: In 1965, Galtung and Ruge initiated a rich strand of academic research on the notion of news values and the practice of gatekeeping in a context

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…These headlines clearly depict the real intention behind framing the two similar scenarios with two different strategies. Joye et. al.…”
Section: Significance Of Studymentioning
confidence: 99%
“…These headlines clearly depict the real intention behind framing the two similar scenarios with two different strategies. Joye et. al.…”
Section: Significance Of Studymentioning
confidence: 99%
“…News selection is fundamental in the journalistic process (Reese, 2001;Tuchman, 1973). Although journalists themselves (Schultz, 2007) and early studies on the selection process suggest that its result depends highly on the individual characters of the journalists (White, 1950;Henningham, 1997), a currently well-established research tradition suggests that there is a stable pattern that can be identified in all of these individual news selection decisions (Caple and Bednarek, 2013;Eilders, 2006;Galtung and Ruge, 1995;O'Neill, 2001, 2017;Joye, Heinrich, and Wohlert, 2016). This tradition is based on the news factor theory, which was introduced by Galtung and Ruge (1965) and combines individual perspectives with professional and organizational routines and cultural influences (Eilders, 2006;Harcup and O'Neill, 2001;Schwarz, 2006).…”
Section: News Factor Theorymentioning
confidence: 99%
“…Various catalogues of news factors have been applied in research (see Appendix 1). As the original taxonomy by Galtung and Ruge (1965) was developed in the context of international news and is over half a century old, researchers have altered and elaborated on this classification to be able to apply it to other types of news (Harcup and O'Neill, 2001;Maier and Ruhrmann, 2008) and changing news production and consumption contexts (Harcup and O'Neill, 2017;Joye et al, 2016). In response to critique that the news factor theory neglects external factors, others have added these factors (Caple and Bednarek, 2013).…”
Section: News Factor Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, scholars have argued that news factors may shift and diversify over time (Kepplinger 2008;Wilke 1984), especially when considering the media change over the past decades due to digitization and the emergence of social media (Harcup and O'Neill 2017). However, research into news values has not sufficiently factored in the media change occurring in the last decades since the early studies were conducted (Joye, Heinrich, and Wöhlert 2015;Kilgo et al 2018).…”
Section: Introductionmentioning
confidence: 99%